Eficiencia de la aplicación de bioestimulantes por medio de inyección, al drench de la planta y nivel foliar en el cultivo de banano (Musa sp.) Valencia, Provincia de Los Ríos. - Mendoza Corro, Edwin Leonel (2015)
This research was carried out in the grounds of the estate Galicea. Located in Canton Valencia - La Union province of Los Rios. Geographic coordinates 79 28 'west longitude and 01 06' south latitude, at an altitude of 120 meters. The overall objective was to evaluate the effect of three bioestimulantes and applied by injection, Drech and foliar, at field level to potentiate the crop yield in banana (Musa sp AAA) and specific: a) Determine the effect of treatments on the growth and productivity of banana cultivation, b) Determine the most efficient treatment in the production of exportable fruit c) Perform economic analysis of the cost of treatments depending on the level of performance; subject to the assumptions: a) applications bioestimulantes achieved higher productivity in planting b) One of the treatments presented better results from the time of application. The study treatments were: Cytokin injection, drench Cytokin, Cytokin Foliar, Kelpax Injection, Kelpax Drench, Kelpax Foliar, ADMF Injection, WNS Drench, ADMF Foliar and control without application. Completely randomized design, with 10 treatments in 4 repetitions was used. All study variables were subjected to analysis of variance and comparison of treatment means the Tukey test was used 95% chance to establish statistical difference between treatments. The treatment presented best results in root weight, height silver shaft width, leaf emergence, weight and yield (kg ha-1), especially in the treatment Cytokin injection, which was superior to the other controls used. The application of bioestimulantes helps improve production yields, especially Cytokin Injection, so the higher income obtained.